Subconjunctival Delivery of Sorafenib-Tosylate-Loaded Cubosomes for Facilitated Diabetic Retinopathy Treatment: Formulation Development, Evaluation, Pharmacokinetic and Pharmacodynamic (PKPD) Studies - Sharadha Madhusudhan; Naresh Vishal Gupta; Mohamed Rahamathulla; Saravana Babu Chidambaram; Riyaz Ali M. Osmani; Mohammed Ghazwani; Mohammed Muqtader Ahmed; Syeda Ayesha Farhana; Mohammed Y. Sarhan; Ahmed Hediyal Tousif (MDPI AG, 2023)
Diabetic retinopathy (DR) is a microvascular complication associated with vascular endothelial growth factor (VEGF) overexpression. Therapeutic delivery to the retina is a challenging phenomenon due to ocular biological barriers. Sorafenib tosylate (ST) is a lipophilic drug with low molecular weight, making it ineffective at bypassing the blood-retinal barrier (BRB) to reach the target site. Cubosomes are potential nanocarriers for encapsulating and releasing such drugs in a sustained manner. The present research aimed to compare the effects of sorafenib-tosylate-loaded cubosome nanocarriers (ST-CUBs) and a sorafenib tosylate suspension (ST-Suspension) via subconjunctival route in an experimental DR model. In this research, ST-CUBs were prepared using the melt dispersion emulsification technique. The distribution of prepared nanoparticles into the posterior eye segments was studied with confocal microscopy. The ST-CUBs were introduced into rats' left eye via subconjunctival injection (SCJ) and compared with ST-Suspension to estimate the single-dose pharmacokinetic profile. Streptozotocin (STZ)-induced diabetic albino rats were treated with ST-CUBs and ST-Suspension through the SCJ route once a week for 28 days to measure the inhibitory effect of ST on the diabetic retina using histopathology and immunohistochemistry (IHC) examinations. Confocal microscopy and pharmacokinetic studies showed an improved concentration of ST from ST-CUBs in the retina. In the DR model, ST-CUB treatment using the SCJ route exhibited decreased expression levels of VEGF, pro-inflammatory cytokines, and adhesion molecules compared to ST-Suspension. From the noted research findings, it was concluded that the CUBs potentially enhanced the ST bioavailability. The study outcomes established that the developed nanocarriers were ideal for delivering the ST-CUBs via the SCJ route to target the retina for facilitated DR management.